Alcohol consumption, types of alcoholic beverages and risk of Venous Thromboembolism : the Tromsø Study - Hansen-Krone, Ida Johanne; Brækkan, Sigrid K.; Enga, Kristin F.; Wilsgaard, Tom; Hansen, John-Bjarne (Universitetet i Tromsø, 2011)
Moderate alcohol consumption has been shown to protect against cardiovascular diseases. The association between alcohol consumption, especially types of alcoholic beverages, and venous thromboembolism (VTE) is less well described. The aim of this study was to investigate the impact of alcohol consumption and different alcoholic beverages on risk of VTE. Information on alcohol consumption were collected by a self-administrated questionnaire in 26 662 subjects, aged 25-97 years, who participated in the Tromsø Study, in 1994-95. Subjects were followed through September 1, 2007 with incident VTE as the primary outcome. There were 460 incident VTE-events during a median of 12.5 years of follow-up. Total alcohol consumption was not associated with risk of incident VTE. However, subjects consuming ≥3 units of liquor per week had 53% increased risk of VTE compared to teetotalers in analyses adjusted for age, sex, BMI, smoking, diabetes, cancer, previous cardiovascular disease, physical activity and higher education (HR: 1.53, 95% CI: 1.00-2.33). Contrary, subjects with a wine intake of ≥3 u/week had 22% reduced risk of VTE (HR: 0.78, 95% CI: 0.47-1.30), further adjustment for liquor and beer intake strengthened the protective effect of wine (HR: 0.53, 95% CI: 0.30-1.00). Frequent binge drinkers (≥1/week) had a 17% increased risk of VTE compared to teetotallers (HR 1.17, 95% CI: 0.66-2.09), and a 47% increased risk compared to non-binge drinkers (HR 1.47, 95% CI: 0.85-2.54). In conclusion, liquor consumption and binge drinking was associated with increased risk of VTE, whereas wine consumption was possibly associated with reduced risk of VTE.